PROTOTYPE BAHAN AJAR BAHASA INDONESIA BERORIENTASI DUNIA KERJA KEPARIWISATAAN UNTUK SISWA KELAS X SMK - nurjaya, gede (LPPM Undiksha, 2017)
This research and development was done with the aim of developing tourism sector oriented instructional material for the tenth grade students at SMK Program Keahlian UPW in Denpasar City. To achieve the aim, a study was done to identify the tourism instructional material and Indonesian material that is relevant to the development of Indonesian instructional material for the tenth grade students at SMK Program Keahlian Usaya Pelayanan Wisata in Denpasar City. In the second year, using document analysis method and panel group discussion, Indonesian instructional material for the tenth grade students at SMK Program Keahlian Usaya Pelayanan Wisata in Denpasar City had been developed The basic framework of the material is as follows: (1) the use of thematic approach to cover the theme of tourism in the Indonesian textbook, (2) the use of text based Indonesian instructional material development, (3) the use of scientific approach in implementing text based instructional material. The prototype designed has good validity when it was judged by relevant judges. With the findings, it is suggested that in developing instructional material with other orientations the instructional material development has to be adapted to the design of the prototype found in this study.